The association between sleep duration, snoring and prevalent type 2 diabetes mellitus with regard to gender and menopausal status: the CKB study in Zhejiang rural area, China - Wu, H; Wang, H; Hu, R; Zhong, J; Qian, Y; Wang, C; Xie, K; Chen, L; Gong, W; Guo, Y; Bian, Z; Chen, Z; et al. (Springer Verlag, 2016)
To evaluate the association between sleep duration, snoring and diabetes according to gender and menopausal status in rural China.The data were part of the baseline survey of China Kadoorie Biobank, from a rural county in the south-east costal Zhejiang province. Participants including 24,027 men and 33,677 women aged 30-79 years were enrolled during 2004-2008. Multivariable logistic regression was used to calculate adjusted odds ratios (ORs) and 95 % confidence intervals (CIs) for diabetes.Sleep duration was shown to have a U-shaped association with diabetes in women, in particular in postmenopausal women after adjustment for potential confounders. Compared with 7-h sleepers, ORs (95 % CIs) of sleep duration ≤5 and ≥10 h for diabetes were 1.32 (1.02-1.69) and 1.30 (1.03-1.65), respectively, in postmenopausal women (P for quadratic trend = 0.016). However, this U-shaped association was not obvious in men and premenopausal women. Frequently snoring was positively associated with diabetes in all participants. However, this association was not independent of socioeconomic status, health behaviors, obesity and chronic diseases. With increasing sleep duration, the proportion of frequently snoring increased in all participants (P trend <0.05). Postmenopausal women had 23 % (95 % CI 6-44 %) higher odds of diabetes compared with premenopausal women, and the duration of menopause had cumulative effects on diabetes.Short and long sleep durations were significantly associated with diabetes in postmenopausal women, independent of potential confounders. The proportion of frequently snoring had linear trend with sleep duration. Postmenopausal status and the duration of menopause increased the odds of diabetes.